Company Attractiveness, Corporate Reputation, and Recruitment Websites as Determinants of Job Application Intentions (Case Study of Islamic Banking Study Program Students) - Tri Puji Astuti (Journal of Business Management and Islamic Banking, 2024)
Research Aims: The research aims to examine and analyze the influence of company attractiveness, company reputation and recruitment website on job application intentions in the sharia banking industry. Methodology: The respondents were sharia banking students in Yogyakarta, with a sampling technique using purposive sampling with a total sample of 145 respondents. The analysis tool used is WarpPLS 7.0. Research Findings: The results of the research show that company attractiveness has a positive and significant effect on intention to apply, company reputation and recruitment website do not have a significant effect on intention to apply for work and recruitment websites are proven to be able to moderate the influence of company attractiveness and company reputation on job application intentions. Theoretical Contribution: The research findings  identify the factors that serve as strengths, making them attractive to potential applicants based on the Theory of Reasoned Action. Research limitation and implication: Islamic banks in Indonesia should pay closer attention to company attractiveness, particularly regarding the value that potential employees will gain. Similarly, regarding corporate reputation, Islamic banks must continue to maintain their well-established reputation among employees and the surrounding community.